Complete Sanskrit - Coulson, Michael; Revised by Gombrich, Richard; Benson, James (London Teach Yourself, 2015)
Do you want to read Indian classics in the original? Do you want to progress beyond the basics? Do you want to reach a high standard? This work contains original material on Sanskrit syntax and usage. It also includes: examples from actual Sanskrit works, vocabularies into and out of Sanskrit, and explains how to use Sanskrit commentaries.
Include Appendices and Indexes.
A complete course on reading and understanding Sanskrit, designed for absolute beginners, built around authentic religious and historical texts.
Keywords: Sanskrit language -- Sanskrit language--Grammar